ACT001 improves OVX-induced osteoporosis by suppressing the NF-κB/NLRP3 signaling pathway - Yuan Li; Jin-Yu Yang; Ma-Li Lin; Tian-Zhu Liu; Wen-Na Lu; Ying Yang; Zhong-Cheng Liu; Jian-Heng Li; Guo-Qiang Zhang; Jian-Shuang Guo (Molecular Medicine)
Abstract Osteoporosis (OP) is a common systemic metabolic bone disease characterized by the decrease in bone mass and hyperactivity of osteoclasts. ACT001 is approved as an orphan drug by FDA and has shown multiple protective effects against tissue injury. However, its role in prevention of osteoclast differentiation and the underlying mechanisms have not been elucidated. Herein, we show that ACT001 inhibited RANKL-induced osteoclast differentiation and F-actin ring formation through suppressing the expression of Nfatc1, TRAP, Ctsk, Dc-stamp without obvious cytotoxicity in vitro. ACT001 restrained the phosphorylation of NF-κB and the activation of NLRP3 inflammasome, thereby decreased the expression of pyroptosis-related protein. (GSDMD, caspase-1, IL-1β, IL-18). Consistent with ACT001, the NLRP3 inflammasome inhibitor MCC950 treatment also suppressed the osteoclastogenesis through inhibiting the transcriptional activation of Nfatc1. Furthermore, ACT001 protected ovariectomy-induced bone loss in mice, reduced the number of osteoclasts, downregulated the expression of NLRP3 and IL-1β. These data indicate that ACT001 can reduce RANKL-induced osteoclast differentiation through suppressing the NF-κB/NLRP3 pathway, and attenuate the bone loss induced by estrogen-deficiency, suggesting its therapeutic potential for bone homeostasis maintenance and osteoporosis treatment.